Dual-stage chemical looping of microalgae for methanol production with negative-carbon emission. (February 2019) - Nurdiawati, Anissa; Zaini, Ilman Nuran; Aziz, Muhammad
Abstract: As the world is transitioning towards a low-carbon economy, it is becoming important to develop ways to reduce carbon dioxide (CO2 ) emissions. Chemical looping, a low carbon technology for the industry, is considered as a potential breakthrough technology and a viable option for efficient fuel conversion and carbon capture and storage, with the successful completion of pilot plant trials in the USA. The conversion of captured CO2 to methanol can be considered a promising method for significantly reducing CO2 emissions, while the produced methanol can be used as a convenient energy carrier for hydrogen storage. This study focuses on a process of converting microalgae, a potential fuel feedstock, into methanol by utilizing CO2 generated within the process. The specific focus lies on the conversion of the microalgae into methanol through dual-stage chemical looping and efficient process integration with maximum energy recovery. Aspen Plus® was used to simulate the facility producing 42 mt (metric tons) methanol/h using 60.1 mt/h CO2 and 8.2 mt/h H2 . The process was divided into four-module operations: drying, chemical looping gasification, syngas chemical looping, and methanol synthesis. The energy efficiency of this process is around 45–51% which is comparative with the concentrated CO2- based methanol and typical biomass-based syngas to methanol processes. Because the separated CO2 obtained via chemical looping is utilized for methanol synthesis, the carbon-negative value is attained.